DIDACTIC APPROACH TO DESIGNING LESSON PROCESSES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the issue of improving the educational efficiency of school-children. The importance of forming a universal learning movement in students to increase the effectiveness of learning is emphasized.